Privately Managed Public Secondary Schools and Academic Achievement in Trinidad and Tobago: Evidence from Rule-Based Student Assignments - Diether W. Beuermann; C. Kirabo Jackson; Ricardo Sierra (Inter-American Development Bank (IDB), 2015)
Many nations allow private entities to manage publicly funded schools and grant them greater flexibility than traditional public schools. However, isolating the causal effect of attending these privately managed public schools relative to attending traditional public schools is difficult because students who attend privately managed schools may differ in unobservable ways from those who do not. This paper estimates the causal effect on academic outcomes in Trinidad and Tobago as a result of attending privately managed public secondary schools (assisted schools) relative to traditional public secondary schools. In Trinidad and Tobago, students are assigned to secondary schools based on an algorithm that created exogenous variation in school attendance, allowing us to remove self-selection bias. Despite large differences in teacher quality and peer quality across these school types, we find little evidence of any relative benefit in attending an assisted school between the ages of 10 and 15 in terms of dropout rates or examination performance at age 15.
hdl:11319/7308
Keywords: H4; I2; 330; Trinidad and Tobago; school quality; school selectivity; student achievement